Cutting the Bunk: Comparing the Solo and Aggregate Effects of Prebunking and Debunking Covid-19 Vaccine Misinformation. Issue 4 (August 2022) - Amazeen, Michelle A.; Krishna, Arunima; Eschmann, Rob
An online experiment among a nationally representative YouGov sample of unvaccinated U.S. adults ( N = 540) leverages inoculation theory as a preliminary step in uniting the prebunking and debunking literature. By testing how prior attitudes toward Covid-19 vaccines interact with varying message interventions, the study finds that specific inoculation messages protect against misinformation, but only among those with preexisting healthy attitudes. Generic inoculation messages have wider application, offering both prophylactic and therapeutic benefits. However, the therapeutic benefits of generic inoculations disappear when debunking messages are present. Nonetheless, generic inoculations do not appear to have detrimental effects on those infected with unhealthy attitudes, unlike specific inoculation messages. Whether the messages are truly a form of inoculation by generating threat merits further research.